Strategic Candidacy and Voting Procedures - Dutta, Bhaskar; Jackson, Matthew O.; Le Breton, Michel (Econometrica, 2001)
We study the incentives of candidates to strategically affect the outcome of a voting procedure. We show that the outcomes of every nondictatorial voting procedure that satisfies unanimity will be affected by the incentives of noncontending candidates (i.e., who cannot win the election) to influence the outcome by entering or exiting the election.